Comments on the Discussion of Pleban i wieś. Historia życia proboszcza tenczyńskiego z początków XVIII wieku. Studium mikrohistoryczne [Plebanus and the Village: A Microhistorical Study of the Life of the Parish Priest of Tenczyn in the Early 18th Century] - Zamorski, Krzysztof (Sensus Historiae, 2025)
This text serves as a response and commentary on six articles discussing the author’s latest book. It addresses the essence of the concepts of life history and microhistory. It refers to a series of observations concerning the nature of microanalysis. It raises analytical questions regarding the sources used in the work, the aesthetics of the book, and, in particular, the stylistic approach of using archaic language. It contains remarks on the relationship between the adopted style and historical fiction narrative. It responds to allegations of inaccuracies in the interpretation of certain phrases in the source text and the rules for citing historical sources adopted in the book.